Biomass tar-based battery negative electrode carbon material and preparation method thereof, battery negative electrode plate and sodium ion battery

Through a simplified process, fiber-based biomass tar is combined with urea to prepare a battery negative electrode carbon material with a high specific surface area, solving the problems of complex biomass tar conversion process and unstable product in the prior art, and achieving high efficiency and long life of sodium ion batteries.

CN119591085APending Publication Date: 2025-03-11Heilongjiang Boneng Green Energy Technology Group Co., Ltd.
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411849157.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the preparation process of converting biomass tar into battery negative electrode carbon materials is complex, and the products are unstable, making it difficult to meet the high efficiency and long life requirements of sodium ion batteries.

Method used

The biomass tar obtained by pretreatment of fiber-based biomass and urea were stirred in anhydrous ethanol, and then calcined and ball milled to prepare a battery negative electrode carbon material with a high specific surface area. This method simplifies the process flow, reduces costs, and optimizes the pore structure and electrochemical properties of the material by controlling the mass ratio of urea and the calcining temperature.

Benefits of technology

The prepared biomass tar-based battery negative electrode carbon material has excellent electrochemical properties, including high specific surface area, good conductivity and stable structure, which can significantly improve the rate performance and cycle stability of sodium ion batteries, and meet the market demand for high life and long cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591085A_ABST
    Figure CN119591085A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and relates to a biomass tar-based battery negative electrode carbon material, a preparation method thereof, a battery negative electrode plate and a sodium ion battery. The method comprises the following steps: pretreating fiber-based biomass to obtain biomass tar; the method comprises the following steps: dissolving biomass tar and urea in absolute ethyl alcohol, and drying the absolute ethyl alcohol to obtain a raw material; calcining the raw materials to obtain a crude product; and grinding and sieving the crude product to obtain the biomass tar-based battery negative electrode carbon material. The battery negative electrode plate is prepared by the following steps: firstly, uniformly mixing a biomass tar-based battery negative electrode carbon material serving as an active substance with a conductive agent and a binder in proportion, and adding a solvent N-methyl pyrrolidone to form slurry; and coating a copper foil with the slurry, and drying to obtain the copper foil. The sodium ion battery contains the battery negative plate. The invention can effectively make up the defects of limited source, high cost, heavy environmental burden and the like of the traditional carbon material, and also can promote the efficient utilization of biomass energy and the development of circular economy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and relates to a biomass tar-based battery negative electrode carbon material and a preparation method thereof, a battery negative electrode sheet, and a sodium ion battery. Background Art

[0002] Battery negative electrode materials are one of the key factors that determine the performance of sodium-ion batteries. At present, the most common negative electrode materials for sodium-ion batteries are mainly divided into four categories. The first is carbon-based negative electrode materials, mainly including graphite, soft carbon, hard carbon and nanocarbon. Among them, hard carbon has the advantages of abundant raw materials, stable structure, low voltage platform, long charge and discharge cycle life, and excellent safety performance. It has become the first choice for negative electrode materials of sodium-ion batteries, but it also faces the shortcomings of low sodium storage capacity and slow ion diffusion rate; the second is alloy negative electrode materials, which have high theoretical specific capacity, but the volume expansion is serious and the safety is poor during charging and discharging; the third is titanium-based negative electrode materials, which have small volume changes during charging and discharging, but the sodium storage capacity is low; the fourth is organic negative electrode materials, which have a wide variety and low cost, but the disadvantages are low electronic conductivity and poor stability.

[0003] The graphite in carbon-based negative electrode materials can be natural graphite or artificial graphite. Natural graphite is extracted directly from ores and purified and ball-milled. Artificial graphite is obtained by pyrolysis of raw materials such as petroleum coke and needle coke, and graphitization treatment at high temperature. Graphite materials have low cost, high theoretical specific capacity, and stable cycle performance. However, there is a large irreversible capacity loss during the first charge and discharge, and the electrolyte requirements are high. Soft carbon materials are pyrolyzed by pyrolysis of precursor materials such as coal tar pitch and phenolic resin, usually at temperatures below 1000°C. This method has a low cost for preparing negative electrode materials and good compatibility with electrolytes, but the battery specific capacity is lower than that of graphite and the cycle performance is slightly worse. Hard carbon is formed by pyrolysis of organic matter such as polymers and cellulose at a lower temperature and is not easy to graphitize. Using hard carbon materials as negative electrodes can avoid metal deposition, improve safety, and have a more stable potential platform, but the specific capacity is lower and the charge and discharge efficiency is lower than that of graphite. Silicon-based materials Silicon can be made by metal thermal reduction, while silicon-based composite materials (such as Si / C) are prepared by chemical vapor deposition, mechanical alloying or sol-gel method. The theoretical specific capacity is extremely high, much higher than graphite, but the volume changes greatly during charging and discharging, resulting in poor cycle stability. Alloy batteries are prepared by mechanical alloying, electrodeposition or chemical synthesis, such as lithium alloys, tin alloys, etc. High theoretical specific capacity, fast charging and discharging capabilities but fast capacity decay and short cycle life. Lithium titanate is prepared by solid phase reaction method, hydrothermal synthesis or sol-gel method, with excellent cycle performance, fast charging speed, good safety performance, but relatively low specific capacity.

[0004] Biomass tar is a liquid product produced by the pyrolysis of biomass under anoxic or anaerobic conditions. It is a complex mixture containing a large number of organic compounds, such as phenols, ketones, acids, esters, alcohols, furans, pyridines and other heterocyclic compounds. Biomass tar contains a large number of organic compounds, which makes its properties diverse and unstable, and it is prone to polymerization, condensation and other reactions. It has high viscosity, which limits its direct use as a fuel. Due to the acidic components, biomass tar is corrosive to metal equipment. At high temperatures, biomass tar is easy to decompose, producing gas, solid residue and heavy components. Because it contains harmful substances, direct discharge of biomass tar will cause environmental pollution. However, converting biomass tar into carbon materials can not only realize waste resource utilization, but also through appropriate pyrolysis and activation treatment, biomass tar can be converted into porous carbon materials with high specific surface area, which is a very important property for electrode materials, adsorbents and catalysts. The control of conditions during the preparation process can make carbon materials have different pore structures, which is very beneficial for energy storage and conversion, gas adsorption and separation. Compared with traditional carbon sources, such as petroleum coke and needle coke, biomass tar is a carbon source with lower cost, more environmentally friendly and sustainable. Heteroatoms (such as N, S, O) in biomass tar can be introduced into carbon materials to give them additional functions, such as improving electrochemical activity or improving conductivity.

[0005] By converting biomass tar into carbon materials, it can effectively make up for the shortcomings of traditional carbon materials, such as limited sources, high costs, and heavy environmental burdens, while also promoting the efficient use of biomass energy and the development of a circular economy. For example, carbon materials prepared from biomass tar can be used as efficient adsorbents in air purification, water treatment, and other fields; they can also be used as electrode materials for supercapacitors, lithium-ion batteries, and sodium-ion batteries to improve energy density and cycle life.

[0006] Patent document CN 115849333 A discloses a method for preparing a bamboo-based hard carbon active electrode material, wherein the bamboo raw material is pretreated in acid solution A to obtain a pretreated bamboo raw material; the pretreated bamboo raw material is pyrolyzed to obtain pyrolyzed bamboo charcoal, and bamboo tar in the pyrolysis process is collected; the pyrolyzed bamboo charcoal is treated with alkali solution B and acid solution C in any order to obtain pretreated bamboo charcoal; bamboo tar and a cross-linking agent are used as precursor raw materials for cross-linking treatment to obtain a carbon shaping agent; the carbon shaping agent or its precursor raw material is mixed with the pretreated bamboo charcoal to obtain a mixture, and then a two-stage roasting treatment is performed to obtain the bamboo-based hard carbon active electrode material. The document also includes the prepared materials and their application in sodium ion batteries. The preparation process requires acid and alkali treatment, and requires secondary roasting after cross-linking treatment. The whole process is complicated and not conducive to environmental protection.

[0007] Patent document CN 117352728 A discloses a hard carbon material and its preparation method and battery, aiming to solve the technical problem that the existing hard carbon material has a high ash content, resulting in low stability and capacity of the battery. The tar is solidified to obtain solidified particles; the solidified particles are pre-carbonized to obtain pre-carbonized powder; the pre-carbonized powder is calcined to obtain the hard carbon material. Acid and alkali treatment is also required for heteroatom organic cross-linking.

[0008] Biomass resources are a renewable resource with the advantages of abundant sources and low cost. However, the research on its direct application in the preparation of battery negative electrode materials is still in its early stages. Existing biomass tar conversion methods usually have problems such as complex preparation process and unstable products.

[0009] Therefore, it is necessary to provide a simple and efficient method to prepare carbon materials with good electrochemical properties using biomass tar to solve the problems existing in the prior art. Summary of the invention

[0010] Based on this, the purpose of the present invention is to provide a method for preparing biomass tar-based battery negative electrode carbon materials, which converts biomass tar into battery negative electrode carbon materials with high specific surface area, which can effectively make up for the shortcomings of traditional carbon materials such as limited sources, high costs, and heavy environmental burdens, while also promoting the efficient utilization of biomass energy and the development of a circular economy.

[0011] The present invention also provides a battery negative electrode sheet and a sodium ion battery comprising the battery negative electrode carbon material, and the sodium ion battery has excellent electrochemical performance.

[0012] To achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a biomass tar-based battery negative electrode carbon material, comprising the following steps: S1, pre-treating fiber-based biomass to obtain biomass tar; S2, dissolving the biomass tar and urea in anhydrous ethanol, and drying the anhydrous ethanol to obtain a raw material; S3, calcining the raw material to obtain a crude product; S4, grinding the crude product to obtain a raw material.

[0013] Furthermore, the fiber-based biomass in S1 includes poplar chips, which are dried at 105±10°C and then gasified at 650±20°C using water vapor as a gasifying agent to obtain primary tar, which is purified and impurity-removed to obtain biomass tar.

[0014] Furthermore, the biomass tar mainly contains 65-68% of C element, 4-7% of H element, 21-26% of O element, 3-6% of N element and 0.5-0.8% of S element; mainly includes 32-36% of phenolic compounds, 28-32% of ketone compounds, 4-7% of hydrocarbon compounds, and the remainder is other heterocyclic compounds; the percentages are mass percentages.

[0015] Furthermore, the preferred biomass tar mainly contains 65% of C element, 6% of H element, 24% of O element, 4% of N element and 0.63% of S element; mainly includes 34.94% of phenolic compounds, 30.01% of ketone compounds, 5.56% of hydrocarbon compounds, and the remainder is other heterocyclic compounds; the percentages are mass percentages.

[0016] Furthermore, the mass ratio of the biomass tar to urea in S2 is 1:0.3-4, and the mass of the anhydrous ethanol is 3-5 times the total mass of the biomass tar and urea; stirring at 60-80°C until the anhydrous ethanol is completely volatilized, and then the obtained product is placed at 105±10°C and dried to constant weight to obtain a raw material.

[0017] Further, the raw materials described in S3 are put into an atmosphere furnace, heated to a calcination temperature of 600-1600° C., kept at a constant temperature for 90±10 min, and then cooled naturally.

[0018] Furthermore, the initial temperature of the atmosphere furnace in S3 is 10±1°C, and the heating rate is 5-8°C / min.

[0019] Furthermore, the ball milling conditions are: the coarse product is ball milled for 4±0.5h at a ball mill speed of 460±5r / min to obtain a powdered material; the powdered raw material screening conditions are: screening with a 300±10 mesh filter.

[0020] The present invention further provides a biomass tar-based battery negative electrode carbon material prepared by the above method, the particle size is mainly 3-5nm, preferably 4nm, which is higher than the common average particle size of 2nm. The material has abundant micropores and a specific surface area of ​​25.29 m 2 / g, and the mesopore ratio is 35%, indicating that the introduction of urea produces a soft template effect on the condensation of bio-tar.

[0021] The present invention further provides a battery negative electrode sheet, which uses biomass tar-based battery negative electrode carbon material as an active material.

[0022] Furthermore, the active material, the conductive agent and the binder are first mixed at a mass ratio of 7-9:1:1, and a solvent N-methylpyrrolidone is added to form a negative electrode slurry; the negative electrode slurry is then coated on a copper foil, and a battery negative electrode sheet is prepared after drying.

[0023] Furthermore, the active material, the conductive agent and the binder are fully mixed by grinding, and N-methylpyrrolidone is added and stirred for 2±0.5h to form a negative electrode slurry. The negative electrode slurry is evenly applied on the copper foil, placed in an oven at 120±10°C for 4-6h, and then taken out to obtain a negative electrode sheet of the battery; the conductive agent is preferably a SuperP conductive agent, and the binder is preferably a PVDF battery binder.

[0024] Finally, the present invention provides a sodium ion battery, which contains the battery negative electrode sheet provided by the present invention. The sodium ion battery is obtained by assembling the battery negative electrode sheet with a sodium positive electrode, a separator, an electrolyte, etc.

[0025] The beneficial effects of the present invention are: 1. The present invention uses the biomass tar obtained after processing fiber-based biomass as the preparation of carbon materials for sodium ion batteries, which can effectively make up for the shortcomings of traditional carbon materials such as limited sources, high costs, and heavy environmental burdens, while also promoting the efficient utilization of biomass energy and the development of a circular economy.

[0026] 2. The present invention uses biomass tar as the main raw material and urea as the auxiliary raw material, does not require additional ingredients, has a simple preparation process, high production efficiency and low cost, and is easy to promote and apply on a large scale.

[0027] 3. The present invention controls the mass of urea added to biomass tar, the heating rate during calcination and the calcination temperature, so that the material prepared has a reasonable pore structure and a large specific surface area. When used as a sodium ion negative electrode material, it can give sodium ion batteries excellent electrochemical properties.

[0028] 4. The sodium ion battery of the present invention has good rate performance and cycle stability, and can meet the market demand for high life and long cycle of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Attached Figure 1 This is a schematic diagram of the preparation process of the biomass tar-based battery negative electrode carbon material in an embodiment of the present invention; Attached Figure 2 This is a SEM analysis diagram of the biomass tar-based battery negative electrode carbon material in an embodiment of the present invention; Attached Figure 3This is an XRD analysis diagram of the biomass tar-based battery negative electrode carbon material in an embodiment of the present invention; Attached Figure 4 This is a Raman spectrum analysis diagram of the biomass tar-based battery negative electrode carbon material in an embodiment of the present invention; Attached Figure 5 Schematic diagram of the preparation process of the negative electrode sheet of the battery in the embodiment of the present invention; Attached Figure 6 Schematic diagram of the preparation process of a sodium ion battery in an embodiment of the present invention; Attached Figure 7 A diagram of the assembly process of a sodium ion battery in an embodiment of the present invention; Attached Figure 8 The figure is a rate performance analysis diagram of the sodium ion battery in the embodiment of the present invention, wherein the upper figure is a material performance comparison diagram prepared at different raw material ratios at the same calcination temperature, and the lower figure is a material performance comparison diagram prepared at different calcination temperatures at the same raw material ratio; Attached Fig. 9 This is a diagram for analyzing the cycle performance of a sodium ion battery in an embodiment of the present invention. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. The embodiments mentioned are all implemented on the premise of the technical solutions of the present invention, and detailed implementation processes are given, but it should be stated that the protection scope of the present invention is not limited to the following embodiments.

[0032] The preparation of the biomass tar-based battery negative electrode carbon material, the preparation of the battery negative electrode sheet, the preparation of the sodium ion battery and the assembly process of the sodium ion battery in the embodiment of the present invention are respectively as follows: Figure 1 , Figure 5 , Figure 6 and Figure 7 shown.

[0033] Example 1 1. Preparation of biomass tar-based battery negative electrode carbon materials (such as Figure 1 Schematic diagram of the preparation process shown) The poplar wood chips are dried to reduce the moisture content, and then gasified at 650°C with water vapor as the gasification agent to obtain biomass tar, which is then purified to remove impurities and improve the purity of the tar.

[0034] Biomass tar and urea were placed in 3 times the mass of anhydrous ethanol (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) at a mass ratio of 1:0.5, and stirred in a 60°C oil bath until the ethanol was completely evaporated. The obtained product was then placed in an oven at 105°C and dried to constant weight to obtain a raw material.

[0035] Take an appropriate amount of dried raw materials, weigh the mass and put them into a square crucible, move them to an atmosphere furnace, set the initial temperature to 10°C, and heat the samples to 1000°C at a heating rate of 5°C / min and keep them at a constant temperature for 90 min for carbonization. After calcination, wait for natural cooling, collect the crude product and ball mill it at a ball mill speed of 460r / min for 4h to obtain a powdered material; then sieve the powdered raw material with a 300-mesh filter to obtain a biomass tar-based battery negative electrode carbon material, which is marked as NT0.5-1000.

[0036] 2. Preparation of battery negative electrode sheets and sodium ion batteries (such as Figure 5-7 Schematic diagram of the preparation and assembly process shown) 0.16g of NT0.5-1000, 0.02g of SuperP conductive agent and 0.02g of PVDF battery binder were mixed and ground, 100g of organic solvent N-methylpyrrolidone was added and stirred for 2h, and finally evenly applied on copper foil with a coating thickness of 150μm. After being placed in an oven at 120℃ for 4h, the battery negative electrode was obtained.

[0037] The negative electrode sheet of the battery was cut into pieces with a diameter of 14 mm using a slicer, and the sodium ion button battery was assembled in the order of negative electrode shell, sodium sheet (diameter 12 mm), diaphragm, electrolyte, negative electrode sheet of the battery, gasket, spring sheet, and positive electrode shell in an argon atmosphere glove box. The sodium ion battery diaphragm was a glass fiber diaphragm Whatman GF / D round (1820), and the electrolyte was 1MNaPF6 inDIGLYME.

[0038] Example 2 1. Preparation of biomass tar-based battery negative electrode carbon materials The poplar wood chips are dried to reduce the moisture content, and then gasified at 650°C with water vapor as the gasification agent to obtain biomass tar, which is then purified to remove impurities and improve the purity of the tar.

[0039] Biomass tar and urea were placed in 3 times the mass of anhydrous ethanol (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) at a mass ratio of 1:1, and stirred in a 60°C oil bath until the ethanol was completely evaporated. The obtained product was then placed in an oven at 105°C and dried to constant weight to obtain a raw material.

[0040] Take an appropriate amount of dried raw materials, weigh the mass and put them into a square crucible, move them to an atmosphere furnace, set the initial temperature to 10°C, and heat the samples to 1000°C at a heating rate of 5°C / min and keep them at a constant temperature for 90 min for carbonization. After calcination, wait for natural cooling, collect the crude product and ball mill it at a ball mill speed of 460r / min for 4h to obtain a powdered material; then sieve the powdered raw material with a 300-mesh filter to obtain a biomass tar-based battery negative electrode carbon material, which is labeled NT1-1000.

[0041] 2. Preparation of battery negative electrode sheets and sodium ion batteries Mix and grind 0.16g of NT1-1000, 0.02g of SuperP conductive agent, and 0.02g of PVDF battery binder, add 100g of organic solvent N-methylpyrrolidone and stir for 2h, finally evenly apply it on copper foil with a coating thickness of 150μm, place it in an oven at 120℃ for 4h and then take it out to obtain the battery negative electrode sheet.

[0042] The negative electrode sheet of the battery was cut into pieces with a diameter of 14 mm using a slicer, and the sodium ion button battery was assembled in the order of negative electrode shell, sodium sheet (diameter 12 mm), diaphragm, electrolyte, negative electrode sheet of the battery, gasket, spring sheet, and positive electrode shell in an argon atmosphere glove box. The sodium ion battery diaphragm was a glass fiber diaphragm Whatman GF / D round (1820), and the electrolyte was 1MNaPF6 inDIGLYME.

[0043] Example 3 1. Preparation of biomass tar-based battery negative electrode carbon materials The poplar wood chips are dried to reduce the moisture content, and then gasified at 650°C with water vapor as the gasification agent to obtain biomass tar, which is then purified to remove impurities and improve the purity of the tar.

[0044] Biomass tar and urea were placed in 3 times the mass of anhydrous ethanol (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) at a mass ratio of 1:2, and stirred in a 60°C oil bath until the ethanol was completely evaporated. The obtained product was then placed in an oven at 105°C and dried to constant weight to obtain a raw material.

[0045] Take an appropriate amount of dried raw materials, weigh the mass and put them into a square crucible, move them to an atmosphere furnace, set the initial temperature to 10°C, and heat the samples to 1000°C at a heating rate of 5°C / min and keep them at a constant temperature for 90 min for carbonization. After calcination, wait for natural cooling, collect the crude product and ball mill it at a ball mill speed of 460r / min for 4h to obtain a powdered material; then sieve the powdered raw material with a 300-mesh filter to obtain a biomass tar-based battery negative electrode carbon material, which is labeled NT2-1000.

[0046] 2. Preparation of battery negative electrode sheets and sodium ion batteries 0.16g of NT2-1000, 0.02g of SuperP conductive agent and 0.02g of PVDF battery binder were mixed and ground, 100g of organic solvent N-methylpyrrolidone was added and stirred for 2h, and finally evenly applied on copper foil with a coating thickness of 150μm. After being placed in an oven at 120℃ for 4h, the battery negative electrode was obtained.

[0047] The negative electrode sheet of the battery was cut into pieces with a diameter of 14 mm using a slicer, and the sodium ion button battery was assembled in the order of negative electrode shell, sodium sheet (diameter 12 mm), diaphragm, electrolyte, negative electrode sheet of the battery, gasket, spring sheet, and positive electrode shell in an argon atmosphere glove box. The sodium ion battery diaphragm was a glass fiber diaphragm Whatman GF / D round (1820), and the electrolyte was 1MNaPF6 inDIGLYME.

[0048] Example 4 1. Preparation of biomass tar-based battery negative electrode carbon materials The poplar wood chips are dried to reduce the moisture content, and then gasified at 650°C with water vapor as the gasification agent to obtain biomass tar, which is then purified to remove impurities and improve the purity of the tar.

[0049] Biomass tar and urea were placed in 3 times the mass of anhydrous ethanol (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) at a mass ratio of 1:3, and stirred in a 60°C oil bath until the ethanol was completely evaporated. The obtained product was then placed in an oven at 105°C and dried to constant weight to obtain a raw material.

[0050] Take an appropriate amount of dried raw materials, weigh the mass and put them into a square crucible, move them to an atmosphere furnace, set the initial temperature to 10°C, and heat the samples to 1000°C at a heating rate of 5°C / min and keep them at a constant temperature for 90 min for carbonization. After calcination, wait for natural cooling, collect the crude product and ball mill it at a ball mill speed of 460r / min for 4h to obtain a powdered material; then sieve the powdered raw material with a 300-mesh filter to obtain a biomass tar-based battery negative electrode carbon material, which is labeled NT3-1000.

[0051] 2. Preparation of battery negative electrode sheets and sodium ion batteries 0.16g of NT3-1000, 0.02g of SuperP conductive agent and 0.02g of PVDF battery binder were mixed and ground, 100g of organic solvent N-methylpyrrolidone was added and stirred for 2h, and finally evenly applied on the copper foil with a coating thickness of 150μm. After being placed in an oven at 120℃ for 4h, the battery negative electrode was obtained.

[0052] The negative electrode sheet of the battery was cut into pieces with a diameter of 14 mm using a slicer, and the sodium ion button battery was assembled in the order of negative electrode shell, sodium sheet (diameter 12 mm), diaphragm, electrolyte, negative electrode sheet of the battery, gasket, spring sheet, and positive electrode shell in an argon atmosphere glove box. The sodium ion battery diaphragm was a glass fiber diaphragm Whatman GF / D round (1820), and the electrolyte was 1MNaPF6 inDIGLYME.

[0053] Example 5 1. Preparation of biomass tar-based battery negative electrode carbon materials The poplar wood chips are dried to reduce the moisture content, and then gasified at 650°C with water vapor as the gasification agent to obtain biomass tar, which is then purified to remove impurities and improve the purity of the tar.

[0054] Biomass tar and urea were placed in 3 times the mass of anhydrous ethanol (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) at a mass ratio of 1:2, and stirred in a 60°C oil bath until the ethanol was completely evaporated. The obtained product was then placed in an oven at 105°C and dried to constant weight to obtain a raw material.

[0055] Take an appropriate amount of dried raw materials, weigh the mass and put them into a square crucible, move them to an atmosphere furnace, set the initial temperature to 10°C, and heat the samples to 800°C at a heating rate of 5°C / min and keep them at a constant temperature for 90 min for carbonization. After calcination, wait for natural cooling, collect the crude product and ball mill it at a ball mill speed of 460r / min for 4h to obtain a powdered material; then sieve the powdered raw material with a 300-mesh filter to obtain a biomass tar-based battery negative electrode carbon material, which is labeled NT2-800.

[0056] 2. Preparation of battery negative electrode sheets and sodium ion batteries 0.16g of NT2-800, 0.02g of SuperP conductive agent and 0.02g of PVDF battery binder were mixed and ground, 100g of organic solvent N-methylpyrrolidone was added and stirred for 2h, and finally evenly applied on copper foil with a coating thickness of 150μm. After being placed in an oven at 120℃ for 4h, the battery negative electrode was obtained.

[0057] The negative electrode sheet of the battery was cut into pieces with a diameter of 14 mm using a slicer, and the sodium ion button battery was assembled in the order of negative electrode shell, sodium sheet (diameter 12 mm), diaphragm, electrolyte, negative electrode sheet of the battery, gasket, spring sheet, and positive electrode shell in an argon atmosphere glove box. The sodium ion battery diaphragm was a glass fiber diaphragm Whatman GF / D round (1820), and the electrolyte was 1MNaPF6 inDIGLYME.

[0058] Example 6 1. Preparation of biomass tar-based battery negative electrode carbon materials The poplar wood chips are dried to reduce the moisture content, and then gasified at 650°C with water vapor as the gasification agent to obtain biomass tar, which is then purified to remove impurities and improve the purity of the tar.

[0059] Biomass tar and urea were placed in 3 times the mass of anhydrous ethanol (analytical grade, Sinopharm Chemical Reagent Co., Ltd.) at a mass ratio of 1:2, and stirred in a 60°C oil bath until the ethanol was completely evaporated. The obtained product was then placed in an oven at 105°C and dried to constant weight to obtain a raw material.

[0060] Take an appropriate amount of dried raw materials, weigh the mass and put them into a square crucible, move them to an atmosphere furnace, set the initial temperature to 10°C, and heat the samples to 1250°C at a heating rate of 5°C / min and keep the temperature constant for 90 min for carbonization. After calcination, wait for natural cooling, collect the crude product and ball mill it at a ball mill speed of 460r / min for 4h to obtain a powdered material; then sieve the powdered raw material with a 300-mesh filter to obtain a biomass tar-based battery negative electrode carbon material, which is labeled NT2-1250.

[0061] 2. Preparation of battery negative electrode sheets and sodium ion batteries 0.16g of NT2-1250, 0.02g of SuperP conductive agent and 0.02g of PVDF battery binder were mixed and ground, 100g of organic solvent N-methylpyrrolidone was added and stirred for 2h, and finally evenly applied on copper foil with a coating thickness of 150μm. After being placed in an oven at 120℃ for 4h, the battery negative electrode was obtained.

[0062] The negative electrode sheet of the battery was cut into pieces with a diameter of 14 mm using a slicer, and the sodium ion button battery was assembled in the order of negative electrode shell, sodium sheet (diameter 12 mm), diaphragm, electrolyte, negative electrode sheet of the battery, gasket, spring sheet, and positive electrode shell in an argon atmosphere glove box. The sodium ion battery diaphragm was a glass fiber diaphragm Whatman GF / D round (1820), and the electrolyte was 1MNaPF6 inDIGLYME.

[0063] Implementation effect analysis The performance tests were conducted on the biomass tar-based battery negative electrode carbon material and the sodium ion battery in the embodiments of the present invention.

[0064] 1. Performance test and analysis of biomass tar-based carbon materials as battery negative electrodes Figure 2The SEM test results of the material are given. The figure shows that the present invention can prepare biomass tar-based battery negative electrode carbon materials with different structures by controlling different calcination temperatures and different mass ratios of urea and biomass tar. It can be seen from NT2-800, NT2-1000 and NT2-1250 that under different calcination temperature conditions, the materials all present dense fragments. It can be seen from NT0.5-1000, NT1-1000, NT2-1000 and NT3-1000 that when the mass ratio of urea to tar is 0.5, the proportion of large and small fragments is almost the same. As the mass ratio increases, the block size tends to be more uniform. When the mass ratio is 3, the block tends to be more dense, which increases the specific surface area of ​​the material. After being applied to sodium ion batteries, the electrochemical performance of sodium ion batteries can be greatly improved.

[0065] Figure 3 The X-ray diffraction analysis results of the material are given. The XRD experimental data of the present invention is collected using Rigaku Ultima IV of Japan, and the input conditions are wavelength 1.5418, voltage 40 KV, and current 40 mA. The figure shows that the XRD curve of the biomass tar-based battery negative electrode carbon material prepared by the method provided by the present invention has two broad peaks at 2θ=25° and 44°, representing the (002) and (100) crystal planes of the graphite microcrystals of the porous carbon, which are typical characteristics of amorphous carbon. The peak of NT2-1250 appears at a smaller angle than that of other materials, indicating that as the temperature increases, the carbon atoms are more active and the average distance between carbon and carbon increases. When the material is used as a negative electrode sheet active material in a sodium ion battery, the smaller distance between carbon and carbon can accelerate the transmission of ions, enabling faster charging and discharging. The weaker peak height also indicates that the graphite structure of the material is amorphous.

[0066] Figure 4 The Raman spectrum analysis results of the materials are given to analyze the graphitization information and defect degree of the biomass tar-based battery negative electrode carbon material. The Raman spectrometer model used in this experiment is Evolution. The figure shows that all materials have two obvious characteristic peaks, which are located at 1342cm -1 and 1586cm -1 At , they correspond to D and G bands, respectively. The D band represents the defects of carbon atoms, and the G band represents the degree of graphitization of the material. D / I G The value represents the intensity ratio of the D peak and the G peak, which can be used to obtain information about the material. The D peak represents defects in the lattice, so the larger the ratio, the more defects there are in the carbon atom crystal. Figure 4 The data were calculated to obtain the I values ​​of NT0.5-1000, NT1-1000, NT / 2-1000, and NT / 3-1000. D / IG The ratios are 0.841, 0.848, 0.851, and 0.850, respectively. It can be seen that the biomass tar-based battery negative electrode carbon materials prepared by the method provided by the present invention are all amorphous carbon. The present invention can obtain biomass tar-based battery negative electrode carbon materials with different graphitization degrees by controlling the calcination temperature. The performance of the biomass tar-based battery negative electrode carbon materials is summarized in Table 1 below.

[0067] It can be seen from Table 1 that the average interlayer spacing d of the biomass tar-based battery negative electrode carbon material in the present invention is 002 Between 0.3 and 0.4, I D / I G The value is between 0.83-0.86, the average specific surface area is 25.29 m² / g, the average pore size is 22.36nm, and the nitrogen content is between 1.0-10wt%. The application of materials with this property in sodium ion batteries can give sodium ion batteries excellent electrochemical properties.

[0068] 2. Sodium ion battery performance test analysis The electrochemical performance test of the sodium ion battery of the present invention was carried out, and the charging and discharging information of the battery during the test was collected using the LANHE blue battery test system. The results are as follows: Figure 8 and Fig. 9 shown.

[0069] Figure 8 This is a performance test chart of sodium ion battery rate (1C=250 mA / g), where the upper figure is a performance comparison chart of materials prepared at different raw material ratios at the same calcination temperature, and the lower figure is a performance comparison chart of materials prepared at different calcination temperatures at the same raw material ratio. It can be seen from the figure that each material exhibits excellent capacity retention and reversibility at different rates. Taking NT2-1000 material as an example, its initial specific capacity is 257.5mAh / g, and the reversible specific capacity can reach 274.3mAh / g, 244.2mAh / g, 233.7mAh / g, 212.3mAh / g, 175.2mAh / g, and 133.9mAh / g at current densities of 25mA / g, 50mA / g, 100mA / g, 200mA / g, 500mA / g, and 1000mA / g. After high-rate cycling, at a current density of 25 mA / g, the specific capacity provided by the electrode can still reach above 257.5 mAh / g, showing good reversibility at high rates.

[0070] Attached Fig. 9This is a sodium-ion battery cycle performance analysis chart. It can be seen from the figure that under 0.2C conditions, the coulombic efficiency of all materials remains stably at a high level, indicating that they have good electrochemical properties and good cycle stability. After 50 charge and discharge cycles, the specific capacity of each material can still be maintained at more than 90%. Taking NT2-1000 material as an example, its initial specific capacity is 257.5mAh / g. After 50 cycles, the specific capacity remains at 249.7mAh / g, and the capacity retention rate is as high as 96.97%.

[0071] The electrochemical performance test results of the sodium ion battery of the present invention are summarized in Table 2 below.

[0072] In summary, the present invention uses biomass tar as a single raw material and urea as an auxiliary component. The nitrogen element in urea is introduced into the tar-based material through a pyrolysis reaction. Nitrogen doping can change the electronic structure and chemical properties of the material, thereby improving its conductivity, increasing active sites, and thus improving the electrochemical performance of the material. At the same time, the gas (such as ammonia, carbon dioxide, etc.) produced by the decomposition of urea at high temperature can be used as a pore-forming agent to help form a porous structure in the tar-based material, which is beneficial to the penetration of the electrolyte and the rapid transmission of ions, and further improves the electrochemical performance of the material. Nitrogen doping and the formation of a pore structure act together on the tar-based material, causing its structure to be reconstructed. This reconstructed material has a higher specific surface area, better conductivity, and a more stable structure, making it more suitable as an electrode material for a sodium ion battery.

[0073] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a biomass tar-based battery negative electrode carbon material, characterized in that: The method comprises the following steps: S1, pretreating fiber-based biomass to obtain biomass tar; S2, dissolving the biomass tar and urea in anhydrous ethanol, and drying the anhydrous ethanol to obtain a raw material; S3, calcining the raw material to obtain a crude product; and S4, grinding and screening the crude product.

2. The preparation method according to claim 1, characterized in that The fiber-based biomass in S1 includes poplar wood chips, which are dried at 105±10°C and then gasified at 650±20°C using water vapor as a gasifying agent to obtain primary tar, which is purified and impurity-removed to obtain biomass tar.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the biomass tar to urea in S2 is 1:0.3-4, and the mass of the anhydrous ethanol is 3-5 times the total mass of the biomass tar and urea.

4. The preparation method according to claim 1, characterized in that: The raw materials described in S3 are put into an atmosphere furnace, heated to a calcination temperature of 600-1600°C, kept at a constant temperature for 90±10 minutes, and then cooled naturally.

5. The preparation method according to claim 4, characterized in that: The initial temperature of the atmosphere furnace in S3 is 10±1°C, and the heating rate is 5-8°C / min.

6. The preparation method according to claim 1, characterized in that: The grinding described in S4 includes ball milling, and the ball milling conditions are: ball milling the coarse product at a ball mill speed of 460±5r / min for 4±0.5h to obtain a powdered material; the powdered raw material screening conditions are: screening with a 300±10 mesh filter.

7. A biomass tar-based battery negative electrode carbon material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.

8. A battery negative electrode sheet, characterized in that: The biomass tar-based battery negative electrode carbon material as claimed in claim 7 is used as the active material.

9. The battery negative electrode sheet according to claim 8, characterized in that: The active material, the conductive agent and the binder are firstly mixed in a mass ratio of 7-9:1:1, and a solvent N-methylpyrrolidone is added to form a slurry; the slurry is then coated on a copper foil and dried to obtain the slurry.

10. A sodium ion battery, characterized in that: A battery negative electrode sheet comprising the battery negative electrode sheet according to claim 8 or 9.

Citation Information

Patent Citations

  • Bamboo-based hard carbon active electrode material, preparation thereof and application of bamboo-based hard carbon active electrode material in sodium ion battery

    CN115849333A

  • Hard carbon material, preparation method thereof and battery

    CN117352728A